"Partner in Prime"? Effects of repeated mobile security priming on attachment security and perceived stress in daily life. Issue 6 (2nd November 2019) - Oehler, Manuela; Psouni, Elia
ABSTRACT: Lacking secure attachment representations is associated with vulnerability to mental and physical health problems, perhaps mediated by increased susceptibility to stress and impaired emotion regulation. Even though cognitive representations of self and others tend to favor confirmation over information, research has shown that adult attachment security can be positively influenced. In a randomized control trial using a mixed between- and within-subjects design, participants ( N = 112) were mobile primed with attachment security stimulating visualization tasks, over a 7-day period. Self-reported attachment security was unchanged; however, reduced attachment avoidance and perceived stress and increased resilience and self-compassion scores were obtained up to one week after the last prime. Participants who reported less effort and more pleasure in carrying out the visualization tasks experienced the highest gains. Results highlight the potential of mobile attachment security priming for intervention, but also the differential potential of such intervention for people with different attachment orientations.